Comparison of Efficacy and Safety of TACE Combined with Microwave Ablation and TACE Combined with Cryoablation in the Treatment of Large Hepatocellular Carcinoma. (25th June 2022) - Wang, Yujia; Li, Wei; Man, Wenling; Dong, Xiaolin; Luo, Yinghao; Zhang, Yan; Zhang, Yongchuang; Dong, Chang; Sun, Weiwei; Yang, Po
Abstract : Purpose . To retrospectively evaluate the efficacy and safety of TACE combined with microwave ablation (MWA) and TACE combined with cryoablation (CRA) in the treatment of large hepatocellular carcinoma. Methods . A retrospective analysis was performed on 81 patients with large hepatocellular carcinoma (tumor diameter 5～8 cm cm) who received TACE combined with ablation in our hospital from February 2015 to February 2019. The study patients were divided into TACE combined with MWA group (T-MWA, n  = 41) and TACE combined with CRA group (T-CRA, n  = 40) according to the treatment plan. Overall survival (OS) and progress free survival (PFS) were compared between the two groups, and complications were observed. Survival curves for OS and PFS were constructed by the Kaplan–Meier method. Differences in overall survival were compared using the log-rank test. Results . There was no statistical difference in general conditions between the two groups of patients. The results showed that 30 (73.2%) patients in T-MWA group achieved objective response (OR) and 39 (95.1%) patients achieved disease control (DC), compared with 24 (60.0%) patients in T-CRA group who achieved objective response (OR) and 37 (92.5%) patients who achieved disease control (DC). The median OS was 19.2 months in the T-MWA group and 18.6 months in the T-CRA group (P = 0.64 ). The median PFS was 9.3 months in the T-MWA group and 12.3 months in the T-CRA group (P = 0.6 ). Univariate and multivariate analysis showed that portal vein tumor thrombus (PVTT), intrahepatic tumor diameter, and the number of tumor lesions were common prognostic factors for OS and PFS. In terms of surgery-related complications and adverse reactions, abdominal pain and gastrointestinal reactions were observed in 13 (31.7%) and 11(26.8%) cases in the T-MWA group, while we observed 4 (10.0%) and 2 (5.0%) cases in the T-CRA group, respectively. The difference between the two was statistically significant (P < 0.05 ). Conclusion . TACE combined with MWA and TACE combined with CRA were equally effective in the treatment of large hepatocellular carcinoma. TACE-CRA can effectively reduce the incidence of abdominal pain and gastrointestinal reactions in patients. However, compared with TACE-MWA, TACE-CRA is more likely to cause thrombocytopenia.